Housing and Ageing: Let’s Get Serious - "How Do You Plan for the Future while Addressing Immediate Chaos?" - McCall, Vikki (Social Inclusion, 2020)
This article presents findings from the Housing and Ageing programme conducted in 2018 that investigated how the housing sector can effectively plan for an ageing population. The project took a transdisciplinary approach to focus on new, critical insights into the process of decision making concerning housing and ageing across Scotland, England and Wales. A ‘Serious Game’ methodology was developed that explored over 200 policy maker, practitioner and service user perspectives. This was used as a framework to capture priorities, decisions, negotiations and processes that indicate how a ‘sense of place’ and ‘place belonging’ can influence the development of suitable housing for older people. Key housing provision challenges identified were tackling inequality, preserving autonomy, in(ter)dependence, empowerment and accessibility. Such challenges need consideration when strategically planning for the future. The findings recommend placing housing at the heart of service integration to support the co-production of decisions that emphasise the importance of working together across boundaries within social policy, service and stakeholder groups. A place-based approach can support the perception that we are all stakeholders in ageing.